Capitellidae (Annelida) from the Brazilian Continental Margin (SW Atlantic): new occurrences of three genera and description of new species - Da Silva, Camila Fernanda; Amaral, Antonia Cecilia Zacagnini (Zootaxa, 2022)
The Brazilian Continental Margin hosts several deep seafloor landscapes. However, this deep margin is still poorly studied and monitored, compared to coastal and continental shelf areas, historically limited to areas of particular economic interest. Some studies financed by the Brazilian oil and gas company have been conducted off Southeast (SE) Brazil (Espírito Santo and Campos Basins) as part of the environmental licensing process for resource exploration. Similar results showed that annelid polychaetes dominated on the continental shelf and upper slope. Within a wide bathymetric range, Capitellidae species belonging to three different genera represented new records for Brazil: Mastobranchus Eisig, 1887, Peresiella Harmelin, 1968, and Polymastigos Green, 2002. Mastobranchus braziliensis sp. nov. was found in shallow waters (20–147m) of both Espírito Santo and Campos Basins; Peresiella megapapilata sp. nov. occurred from 21 to 446m of both Espírito Santo and Campos Basins; and Polymastigos profundus sp. nov. inhabited greater depths (990–1361m) of the Espírito Santo Basin only. Three new species are described and compared to other species of the respective genus, the diagnosis of some genera amended and the type material of Mastobranchus loii Gallardo, 1968 redescribed. Although the three genera have the same number of thoracic chaetigers, they present several morphological differences, and the current effort being made is to “translate” those differences into characters to be included on the generic diagnosis of each genus. Additionally, two new morphological characters were proposed for the family, the shape of thoracic chaetigers and depth of intersegmental groove.